PROPORSI SEMEN MUTU 20 MPA PADA BAHU JALAN TANJUNG SELOR-SIMPANG 3 TANJUNG PALAS-SEKATAK BUJI - Muliadi, Heri; Yuliana, Candra (Jurnal Teknologi Berkelanjutan, 2023)
The Tanjung Selor-SP.3 Tanjuung Palas-Sekatak Buji Road and Bridge Preservation Package is one of the packages under the National Road Planning and Supervision Work Unit of the North Kalimantan National Road Implementation Agency (BPJN). One of the activities is road shoulder pavement using a quality of 20 MPa, where in determining it, concrete samples are made for field application using a proportion of 410 kilograms of cement, 932.5 kilograms of size 1-2 aggregate, 233 kilograms of size 2-3 aggregate, 524 kilograms of sand and 205 liters of air.